The Dynamics of Interleukin-10-Afforded Protection during Dextran Sulfate Sodium-Induced Colitis - Cardoso, Ana; Gil Castro, Antonio; Martins, Ana Catarina; Carriche, Guilhermina M.; Murigneux, Valentine; Castro, Isabel; Cumano, Ana; Vieira, Paulo; Saraiva, Margarida (Frontiers in Immunology, 2018)
Inflammatory bowel disease encompasses a group of chronic-inflammatory conditions of the colon and small intestine. These conditions are characterized by exacerbated inflammation of the organ that greatly affects the quality of life of patients. Molecular mechanisms counteracting this hyper-inflammatory status of the gut offer strategies for therapeutic intervention. Among these regulatory molecules is the anti-inflammatory cytokine interleukin (IL)-10, as shown in mice and humans. Indeed, IL-10 signalling, particularly in macrophages, is essential for intestinal homeostasis. We sought to investigate the temporal profile of IL-10 mediated protection during chemically-induced colitis and which were the underlying mechanisms. Using a novel mouse model of inducible IL-10 over-expression (pMT-10), described here, we show that mice pre-conditioned with IL-10 for 8 days before dextran sulfate sodium (DSS) administration developed a milder colitic phenotype. In IL-10 induced colitic mice, Ly6C cells isolated from the lamina propria showed a decreased inflammatory profile. Because our mouse model leads to transcription of the IL-10 transgene in the bone marrow and elevated seric IL-10 concentration, we investigated whether IL-10 could imprint immune cells in a long-lasting way, thus conferring sustained protection to colitis. We show that this was not the case, as IL-10-afforded protection was only observed if IL-10 induction immediately preceded DSS-mediated colitis. Thus, despite the protection afforded by IL-10 in colitis, novel strategies are required, specifically to achieve long-lasting protection.